Pengaruh Pendekatan Saintifik Pada Pembelajaran Seni Budaya Dan Prakarya Terhadap Capaian Akademis Siswa Kelas Iv Di Mi Salafiyah Syafi’iyah Ii Klinterejo Sooko Mojokerto - Didik Supriyanto (Nazhruna: Jurnal Pendidikan Islam, 2019)
This aims of this research is to reveal whether a scientific approach in teaching and learning of art and culture can improve achievement of IV grade students at MI Salafiyah Syafi'iyah II Klinterejo Sooko Mojokerto. Data collection used in this research is some documents of students in the form of activities before and after praticum of _kolase_ that used a scientific approach consisting of learning activity material. Data sources of this research are from educators, observations that have been made during the activity with various media in the collage. The method of data analysis in this research is the quantitative data analysis of experimental research. Based on the results of data analysis known that there is a very significant difference between the value of learning arts and crafts before getting a scientific approach and after a scientific approach. The scientific approach can improve students' achievement and can help students who have low ability, then there is a positive and significant influence between the scientific approach to the learning of arts and culture for IV grade students at MI Salafiyah Syaf'iyah II craft Klinterejo Sooko Mojokerto. Based on the results of this research, it is suggested for the teacher to use scientific approach because it can be used as a way to help students achievement in learning because the scientific approach includes observing, asking, reasoning, trying, and communicating so that students can improve their intellectual abilities, specifically the ability of high level thinking and obtain high learning outcomes.